Delayed Diagnosis of Mirizzi Syndrome - Oladini, Olufunmilola; Zangan, Steven M.; Navuluri, Rakesh (Seminars in Interventional Radiology, 2016)
Biliary obstruction occurs in a wide variety of malignant and benign conditions. The following is a unique case of biliary obstruction caused by external compression of the hepatic duct by a gallstone (Mirizzi syndrome). Owing to unusual imaging characteristics of the stone, the mass was initially mistaken for a malignancy or hepatic pseudoaneurysm. It was not until the patient developed gallstone ileus that the correct diagnosis was made.
Keywords: biliary obstruction; pseudoaneurysm; cholangiocarcinoma; gallstone; Mirizzi syndrome; interventional radiology